Modeling and optimization : theory and applications : MOPTA, Bethlehem, PA, USA, August 2016 Selected Contributions /: theory and applications : MOPTA, Bethlehem, PA, USA, August 2016 Selected Contributions. (2017) - Unknown
No abstract available